Nicotine Dependence Status and Related Demographic Patterns in Cigarette and Water Pipe Consumers in Bushehr City - Roghayeh Chenary; Maliheh Saeedfiroozabadi; Nasrin Shirmohammadi-Khorram (Hamadan University of Medical Sciences, 2020)
Aims: In recent years, the trend towards smoking has increased. According to various studies, many factors increase smoking, and understanding the patterns of increase in these behaviors is important for designing prevention policies and programs. The aim of the present study was to investigate the nicotine dependence status and related demographic patterns in cigarette and water pipe consumers in Bushehr city. Instruments & Methods: In this cross-sectional descriptive-analytic study, 366 people of cigarette and water pipe consumers in Bushehr city in 2017 were selected by convenience sampling method. Data were collected by using the Standard Nicotine Dependence Syndrome Scale (NDSS) and demographic information questionnaire. Data analysis was performed by SPSS 23 software using multilevel logistic regression. Findings: The mean score of nicotine dependence was 46.61±11.18. 61.7% of consumers had moderate dependence. Variables of age, education level, and duration of use were significant predictors of the severity of nicotine dependence (p<0.05). Conclusion: Nicotine dependence is moderate among cigarette and water pipe consumers in Bushehr city and people with a lower level of education, a longer duration of use, and the onset of use at a younger age are more strongly dependent on nicotine.